Literature Review: Manajemen Perubahan, Tantangan Perubahan dan Model Perubahan - Engkos Kosasih; B. Herawan Hayadi; Furtasan Ali Yusuf; M Haidar Husein; Musadad Musadad (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
When it comes to managing change from a human perspective, an approach called change management can be used. Change management has evolved and evolved over the last fifty years. The term "change" refers to the process in which something changes from an initial state to a different or altered state. Changes, problems, and models are discussed in this research. A literature review was used. The results of this study show how important it is to change everyday life. Additionally, changes must take into account the current problems for which the appropriate model is designed, engineered, and managed.